2020
DOI: 10.1155/2020/8857457
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Preconditioned Wharton’s Jelly-Derived Mesenchymal Stem Cells Mitigate Stress-Induced Apoptosis and Ameliorate Human Islet Survival and Function in Direct Contact Coculture System

Abstract: Protection of isolated pancreatic islets against hypoxic and oxidative damage-induced apoptosis is essential during a pretransplantation culture period. A beneficial approach to maintain viable and functional islets is the coculture period with mesenchymal stem cells (MSCs). Hypoxia preconditioning of MSCs (Hpc-MSCs) for a short time stimulates the expression and secretion of antiapoptotic, antioxidant, and prosurvival factors. The aim of the present study was to evaluate the survival and function of human isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the antioxidant effect of the WJ-MSCs pretreated with ATRA was more potent than WJ-MSCs alone, suggesting that ATRA potentiates the antioxidant effect of WJ-MSCs in ischemic kidney tissues. Keshtkar et al [37] found that WJ-MSCs protected the kidney against ischemia-reperfusion injury by reducing oxidative and endoplasmic reticulum stresses via activation of hypoxiainducible factor-1 α (HIF-1α), so in the current study we investigated the effect of WJ-MSCs and its combination with ATRA on the expression of HIF-1α. HIF-1α plays a critical role in cellular oxygen homeostasis and mitochondrial respiration and protects the kidney against cisplatin-induced tubular cell apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antioxidant effect of the WJ-MSCs pretreated with ATRA was more potent than WJ-MSCs alone, suggesting that ATRA potentiates the antioxidant effect of WJ-MSCs in ischemic kidney tissues. Keshtkar et al [37] found that WJ-MSCs protected the kidney against ischemia-reperfusion injury by reducing oxidative and endoplasmic reticulum stresses via activation of hypoxiainducible factor-1 α (HIF-1α), so in the current study we investigated the effect of WJ-MSCs and its combination with ATRA on the expression of HIF-1α. HIF-1α plays a critical role in cellular oxygen homeostasis and mitochondrial respiration and protects the kidney against cisplatin-induced tubular cell apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This stress-induced resistance induction may not only be beneficial by direct exposure, but also beneficial by indirect exposure to co-cultured cells. Hypoxia-preconditioned mesenchymal stem cells or primary hepatocytes were shown to significantly reduce reactive oxygen species (ROS) production and induce pro-apoptotic proteins, such as Bcl-2, to improve islet survival when co-cultured with human islets ( 147 , 148 ). Alternatively, pancreatic islets can be directly preconditioned via strategic drug delivery.…”
Section: Transplant Preconditioningmentioning
confidence: 99%